Kontrol Gerakan Objek 3D Augmented Reality Berbasis Titik Fitur Wajah dengan POSIT - Heri Pratikno (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
Augmented Reality (AR) is a technique in computerscience that combines real world conditions with the computercomputation results in the form of 2D or 3D graphics. In this study,a method and application implementation in Augmented Reality environment with markerless was discussed. In the markerless technique, interaction process between humans and computers becomes more natural and intuitive than the marker based techniques. Markerless techniques applied in this study used facial feature points so that the result is more robust for the head objectdoes not produce light. The main problem in this area of researchis how the process of controlling the 3D object movement does notexperience anomalies such as railroad phenomenon, where the theeyes catch as if the distance between the two railroads narrower atthe farther view. This study used POSIT (Pose from Orthography and Scale with ITeration), where the position and orientation of the 3D objects were projected in orthographic from facial featurepoints with scaling, so the change in the distance between the faceand the webcam were proportional to the big - small changes of 3D objects. The next step was iteration process carried out four to fivetimes to look for the smallest error factor to obtain the best pose.